ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI PADA SISWA SMK NEGERI 1 BUKIT BATU - Marviva Marviva; Gimin Gimin; Mujiono Mujiono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine how interest in continuing education to tertiary institutions and what factors influence the interest in continuing education to tertiary education for students of SMK Negeri 1 Bukit Batu. This study used a quantitative descriptive method and the population in this study were students of class XI, amounting to 93 people using saturated samples. The data analysis technique used was the F test, the coefficient of determination (R2), Uji multiple linear regression. The result of this research is that ideals have an effect on the interest in continuing education to higher education, where the tcount is 4.027 ≥ ttable 1.987 and a significant value is 0.000 ≤ 0.05. The family environment has no effect on the interest in continuing education to higher education where the obtained t count is 1.747 ≤ t table 1.987 and a significant value is 0.084 ≥ 0.50. Peers have no effect on the interest in continuing education to higher education where the obtained t count is 2.109 ≤ t table 1.987 and a significant value of 0.038 ≥ 0.05. The school environment has an effect on the interest in continuing education to higher education where obtained tcount 5.069 ≥ t table 1.987 and a significant value of 0.000 ≤ 0.05. Simultaneously there is a significant influence between ideals, family environment, peers and the school environment where the obtained Fcount value 38.179 ≥ F table 2.47 and a significant value 0.000 ≤ 0.05. Multiple linear regression equation Y = -2.014 + 0.263 X1 + 0.124 X2 + 0.102 X3 + 0.417 X4. The results of the research coefficient of determination (R2) obtained a value of 0.634 or 63.4%, meaning that this indicates that the variables of ideals (X1), family environment (X2), peers (X3), school environment (X4) together provide contribution to learning outcomes was 63.4%, and the rest (36.6%) was influenced by other factors not included in the study.Key Words: Interest In Continuing Education To Tertiary Institutions, Ideals,The Family Environment, Peers, The School Environment